1998
DOI: 10.1046/j.1365-313x.1998.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

C6‐volatiles derived from the lipoxygenase pathway induce a subset of defense‐related genes

Abstract: SummarySix-Carbon (C 6 -) volatiles, including the aldehydes trans-2-hexenal, hexanal and cis-3-hexenal, as well as their corresponding alcohols, are produced from damaged or wounded plant tissue as a product of the enzymatic activity of hydroperoxide lyase (HPL), a component of the lipoxygenase (LOX) pathway. Aerial treatment of Arabidopsis seedlings with 10 µM concentrations of trans-2-hexenal induces several genes known to be involved in the plant's defense response, including phenylpropanoidrelated genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
303
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(316 citation statements)
references
References 64 publications
10
303
0
3
Order By: Relevance
“…Other studies found minor inductions of gene expression after treatment with GLVs. For example, Bate and Rothstein (1998) exposed Arabidopsis seedlings to the GLV E-2-HAL. They found induction of PAL, LOX, and AOS but no induction of PR1 and PR2.…”
Section: Nonprimed Seedlings Exhibit a Stronger Up-regulation Of Defementioning
confidence: 99%
“…Other studies found minor inductions of gene expression after treatment with GLVs. For example, Bate and Rothstein (1998) exposed Arabidopsis seedlings to the GLV E-2-HAL. They found induction of PAL, LOX, and AOS but no induction of PR1 and PR2.…”
Section: Nonprimed Seedlings Exhibit a Stronger Up-regulation Of Defementioning
confidence: 99%
“…syringae, whereas a virulent strain did not lead to such an increase (Croft et al, 1993). Different C6-volatiles have been shown to induce defence related genes and to stimulate phytoalexin accumulation (Zeringue, 1992;Bate and Rothstein, 1998). In transgenic potato plants lacking HPL transcript an increase in aphid performance was observed (Vancanneyt et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These derive from at least three pathways. Green leaf volatiles are products of the enzymatic activity of hydroperoxide lyase (HPL), a component of the lipoxygenase (LOX) pathway, which results in multiple rearrangement of (Z)-3-hexenal (Bate and Rothstein, 1998;Blee, 1998). Terpenoids are synthesized via the isopentenyl pyrophosphate (IPP) intermediate following the classical mevalonate pathway or via an alternative IPP pathway with glyceraldehyde-3-phosopate and pyruvate identified as the direct precursors of IPP (Lichtenthaler et al, 1997).…”
Section: Introductionmentioning
confidence: 99%